The Influence of the Use of the Create Case Studies Method on Student Learning Outcomes in the Subject Ski in Class VII at Private MTS Nahdhatul Islam Manceg - Sidik Sembiring, Muhammad Fajar; Ginting, Nurman (Universitas Ibn Khaldun, 2023)
The aim of this research is to determine student learning outcomes in Islamic cultural history subjects. before and after using the create case studies method and whether or not there is an influence of the create case studies method on student learning outcomes in the Islamic cultural history course in class VII at the Nahdhatul Islam Mancang Private MTs. This research uses quantitative experimental methods, with the research design used is a quasi-experimental design. The subjects in this research were school principals, teachers in Islamic cultural history subjects and all class VII students at MTs Nahdhatul Islam Mancang. This research obtained results that show that there is an influence on the create case studies method through the results of the difference in the average value of the experimental class of 83.16 after the application of student-made image media with the average value of the control class being 70.36. Meanwhile, through hypothesis testing using the T test, the value obtained tcount is 11,127 with a significance of 0.000 < 0.005 then it is stated that there is an influence (Ha) accepted.